1949
DOI: 10.1111/j.1939-0025.1949.tb06563.x
|View full text |Cite
|
Sign up to set email alerts
|

Projective features of contemplative artistic experience.

Abstract: Institute for Psychoanalysis, ChicagoN ORDER to help transcend the pains of life, man has built the spiritual I retreats of religion and art. These are the oldest and least perishable of the institutions with which ci;ilizations proudly ornament themselves. We find peace and comfort there from the cruelty of nature, the asperities of life, and from a world overpopulated with personifications of our unconscious guilts and fears. In viewing the outside world as a symbolic expression of inner reality, art and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1950
1950
1960
1960

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The theories of many writers emphasize the importance of restitution from depression as an unconscious motive in creative activity (4, 12, 13). According to Greenacre (8, 9), Kris (14), and especially Lee (16, 18, 19) who has written extensively on creativity and the projective features of contemplative artistic experience, the creative artist is a more sensitive and perceptive person who is more subject to neurotic depressions than are other people. Much of his cyclic creativity is due to the fact that it is often initiated as a restitutive activity from a depressive reaction in order to regain love from the maternal conscience figure by creating an art work which is invested with love.…”
Section: Psychologic Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The theories of many writers emphasize the importance of restitution from depression as an unconscious motive in creative activity (4, 12, 13). According to Greenacre (8, 9), Kris (14), and especially Lee (16, 18, 19) who has written extensively on creativity and the projective features of contemplative artistic experience, the creative artist is a more sensitive and perceptive person who is more subject to neurotic depressions than are other people. Much of his cyclic creativity is due to the fact that it is often initiated as a restitutive activity from a depressive reaction in order to regain love from the maternal conscience figure by creating an art work which is invested with love.…”
Section: Psychologic Aspectsmentioning
confidence: 99%
“…Through utilizing artistically the element of timelessness in the personalities of the creative person, it is possible to orient the self further in such a way that there can be healing replenishment of the loved image of the self by interacting with and incorporating at a deep level within the self those stimuli which have stood the test of time. Since the beauty in art work is so valued, therefore, the contemplative artistic experience adds value and a form of timelessness to the self‐image (16).…”
Section: Psychologic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…SYCHODYNAMic Studies of nonrq>resentatjonal art suggest that the creations permit expression through symbolism of certain n^ds that cannot be faced directly Stated in classical psychoanal3rtic terms, art provides a channel through which the "id" may communicate with the "tgp" (9) and express fantasies ordinarily excluded from consciousness (4,10) Although often dreamlike m form (1,3), the aesthetic restructuring of reality by the normal artist follows certain objectively established and widely held criteria and transforms personal unconscious experiences into culturally acceptable symbols through which they may be commumcated to others (12,13) In this way the artist gives the observer the q^rtunity of abreacting his own emotional tensions while at the same time guaranteeing safety through the integrated form m which he expresses himself (9) In the case of the psychotic artist (2,12,13) reality has been so transformed in accordance with his private wishes that commimication with others is greatly limited The productions are more often the fragmentary reflections of a fragmented ego that has lost control and can be understood only m the light of the case history The artist has given up the attempt to accept reality or to share his expressions He succumbs to autistic needs, expressing them directly with no attonf^ at reorganization or social reality testing Nonrepresentational art, whether psychotic or normal, serves the purpose of shock absorption. This function is analc^ous to the preparaticm of the hypnotized patient to face material that has not yet broken through resistances to consciousness (16) In formal art therafŵ ith mentally ill patients Hulse (8) observed that by "painting through" symbolically expressed matenal the patient changes frcon nonobjective to more realistic forms A similar trend was reported by Naumburg (U) in her studies of schizophrenic art PROBLEM Since the schizc^hrenic patient is assumed to have suffered a breakdown of the usual ego defenses that ward off the direct impact of unconscious material, he has been regarded as more perceptive of tmconscious meanings in the behavior of others (6) Recent clinical sujqxnt for this hypothesis has been advanced by Rosen (14), who found his recovered patients especially successful at interpreting the significance of bizarre symbols used by other patients.…”
Section: Introductionmentioning
confidence: 99%